Natural guar, xanthan and carboxymethyl-cellulose-based fluids: Potential use to trap and treat hexavalent chromium in the subsurface. Issue 1 (February 2019) - Siwik, Amanda; Pensini, Erica; Elsayed, Abdallah; Rodriguez, Braulio Macias; Marangoni, Alejandro G.; Collier, Christopher M.
Graphical abstract: Highlights: Natural polymers and sodium thiosulfate solutions can reduce Cr(VI) to Cr(III). The solutions gel, and may trap Cr(VI) in the subsurface. The gelation kinetics depend on the polymer used. Before mixing with Cr(VI) and sodium thiosulfate, 1 wt. % guar and CMC were viscous. Before mixing with Cr(VI) and sodium thiosulfate 1 wt. % xanthan was viscoelastic. Abstract: Guar, xanthan and carboxymethyl cellulose sodium salt (CMC), and the reducing agent sodium thiosulfate were used to produce water-based fluids to trap and reduce Cr(VI) to Cr(III) in the subsurface. Before mixing with Cr(VI) and sodium thiosulfate, 1 wt. % guar and CMC formed viscous fluids, whereas 1 wt. % xanthan formed weak viscoelastic fluids. Upon contact with Cr(VI), the viscoelastic moduli of the fluids increased significantly. Gelation was immediate for guar and occurred after ∼20 min and ∼180 min for xanthan and CMC, respectively. The compressional strength of gelled guar-based fluids increased with increasing pH and decreased with salts, but was significant in all water chemistries tested. Once Cr(VI) was reduced to Cr(III) by sodium thiosulfate, it crosslinked xanthan, guar and CMC. The fast gelation of guar-based fluids after contact with Cr(VI) suggest that they may form barriers around Cr(VI) contaminated zones, preventing its migration during reduction to Cr(III).